2016
DOI: 10.1017/s0021932016000055
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Consanguineous Marriages and Affecting Factors in Turkey: A National Survey

Abstract: This study was carried out by the Turkish Republic Ministry of Health to determine the prevalence of consanguineous marriage and its correlates with socio-demographic and obstetric risk factors in women in Turkey. The cross-sectional, national-level study was carried out from October to December 2013. The study population was composed of women between the ages of 15 and 65 years living in Turkey. The sample size was calculated as 9290 houses within Turkey's 81 provinces so as to improve the Turkish rural-urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 34 publications
2
36
0
1
Order By: Relevance
“…We think that this is due to the high rate of consanguineous marriages in Turkey, which causes an increase in the prevalence of rare recessive diseases (13)(14)(15). It has been reported that the consanguineous marriage frequency was 18.5%, and of these, 57.8% were first cousin marriages in Turkey (16). Similar to our results, another study conducted in the Aegean region of Turkey also reported that the leading cause of low vision and blindness was retinal dystrophy in the 18-50-year age group (17).…”
Section: Figure 2 Distribution Of Causes Of Msvi Based On Age Groupssupporting
confidence: 90%
“…We think that this is due to the high rate of consanguineous marriages in Turkey, which causes an increase in the prevalence of rare recessive diseases (13)(14)(15). It has been reported that the consanguineous marriage frequency was 18.5%, and of these, 57.8% were first cousin marriages in Turkey (16). Similar to our results, another study conducted in the Aegean region of Turkey also reported that the leading cause of low vision and blindness was retinal dystrophy in the 18-50-year age group (17).…”
Section: Figure 2 Distribution Of Causes Of Msvi Based On Age Groupssupporting
confidence: 90%
“…However, a general relationship appears to exist among genotype, cellular phenotype (i.e., importation of peroxisomal matrix proteins), and clinical phenotype (24). No comprehensive PEX molecular genetic testing is available in Turkey; we thus lack data on phenotype/genotype correlations.…”
Section: Discussionmentioning
confidence: 99%
“…However, other mutations could be prevalent in that same population, since at least three patients of Turkish origin (though not precisely defined from which region) have been described with a Q295 * nonsense mutation (exon 6) and a clinical presentation similar to the patients described in this manuscript ( 29 , 30 ). Targeted resequencing of the R70W mutation in 68 healthy Turkish individuals from the Istanbul region (results not shown) showed that the allele was absent there, suggesting that it may be geographically confined to the rural provinces of Afyonkarahisar and Eskişehir, where a tradition of consanguineous marriages promotes passing on of recessive disease ( 31 ). At this moment, we have no evidence that the R70W CARD9 mutation would provide any beneficial traits to the population, and its presence could thus be a direct consequence of endogamy within a small and genetically homogenous population, where a detrimental recessive allele became common through the founder effect ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%